(untitled) (Zaporizhzhia Historical Review, 2021)
This article is devoted to naziís policy in social sphere in Reihskommissariat ìUkraineî. Ukrainian selfgovernment institutions played the main role in implementing policy in this sphere. Only these institutions and their social security departments tried to improve the situation in social sphere in this period.